Educational initiatives to improve the job performance of technical high school students - Ponce Fuentes, Nelly Vanessa (2025)
The research addressed the implementation of educational actions aimed at creating learning environments that promote the academic, social, and professional growth of technical high school students. The objective was to strengthen their job performance and preparation for the professional market through the development of technical and practical skills. The study worked with a population of 200 students and 24 teachers, selecting an intentional sample of 50 first- and second-year technical high school students and seven teachers from the accounting department. The study had a mixed approach and descriptive scope, using quantitative and qualitative methods. The techniques included surveys, interviews, observation, and expert opinion, with questionnaires and interview guides as instruments. The results showed significant improvements in technical skills such as accounting, teamwork, decision-making, and professional responsibility. In conclusion, the educational actions implemented reduced difficulties in job performance and strengthened the academic and practical preparation of the students.